TRAINING PROCESSING HERBAL PLANTS TO INCREASE APPLICATION AND IMMUNITY TO CHILDREN IN THE COVID-19 PANDEMIC - Desta Ayu Cahya Rosyida; Solichatin Solichatin; Yuni Khoirul Waroh; Retno Setyo Iswati (International Journal of Engagement and Empowerment, 2021)
The COVID-19 pandemic has had a very negative impact on various sectors, as well as on the health sector. These include nutrition and maternal and child health services. The COVID-19 pandemic has the potential to hinder the access of mothers and children to optimal health services. The decrease in the number of visits to nutrition and Maternal and Child Health (KIA) services has the potential to create new nutrition and health problems. In an effort to fulfill the need for information and health services for school-age children and adolescents in the midst of minimizing the transmission of COVID-19, various adjustments to programs and activities related to their health are needed, one of which is training to make food made from herbal plants to increase appetite as well as immunity in children. The method used is training demonstrating the processing of herbal plants into delicious food for children to consume. The targets were PKK women, residents of the herbal village, Nginden Jangungan Village, Surabaya City, which was attended by 25 PKK women. This activity will be held on June 21-19 July 2021.The results obtained from the training of the Community Training Program increase public knowledge about herbal plant processing, increase appetite and immunity in children. Increase RT/RW community-based activities to jointly develop the use of herbal plants. Conclusion Herbal plants can be processed into food products with many benefits, such as temulawak pudding which increases immunity and appetite in children.